ANALYSIS OF 110V DC BATTERY EQUALIZING TEST AT 150 KV KALIBAKAL SUBSTATION PLN PURWOKERTO - Prasetyo, Wahyu; Mubarok, Rizky; Adzin Murdiantoro, Randi; Nasrulloh, Nasrulloh; Prasetyono, Rizki Noor (Program Studi Teknik Elektro Universitas Peradaban, 2024)
The existence of batteries in the substation functions to maintain the stability and reliability of the DC electrical system, where the protection system on the control panel must not go out. Therefore, routine battery maintenance and testing are needed so that the battery can run properly and optimally. Battery testing is a routine agenda that is carried out every 6 months. For daily maintenance, a visual inspection (vision) can be carried out, while monthly maintenance is carried out in the form of a battery equalizing test which is carried out so that the 110V DC battery remains stable and can supply DC to auxiliary equipment when in an emergency. The test results obtained in this study were that the equalizing test on the 110V DC battery that was carried out obtained the battery results in normal conditions. This is explained, when the battery is connected to the load and the voltage per battery cell is measured in floating charging mode showing an average voltage of 1.34 V DC. When the battery is in equalizing charging mode, the voltage capacity on each battery cell can be said to be normal or stable with a total voltage value of 128.2 V DC and a temperature value of 27 ºC. For the measurement results of each battery cell after equalizing charging, the average voltage value per battery cell is 1.35 V DC with a total voltage of 116 V DC. It can be concluded that the equalizing test on the 110V battery unit 1 of the 150 KV Main Substation is fairly normal and the battery is ready when run in discharge mode